Strategi Pengembangan Bisnis Ikan Guppy: Pendekatan Business Model Canvas - Sri Suhandiah; Mochammad Efryyanto Putra; Januar Wibowo (Universitas Multi Data Palembang, 2026)
The ornamental fisheries sector in Indonesia has significant potential, including the Guppy (Poecilia Reticulata). FreeFish, an ornamental fish farming business based in Surabaya, faces challenges in marketing and expanding its market reach, despite having a high production capacity. This study aims to formulate a business development strategy using the Business Model Canvas (BMC) approach. The method used is descriptive qualitative with a case study on the FreeFish business, through observation, interviews, and surveys of 50 FreeFish customers. The results indicate that marketing strategies, including TikTok content, collaboration with streamers, event participation, and bundling sales, have a significant positive impact on increasing sales and expanding market reach. The BMC approach has proven effective in supporting the development of the fish business and increasing the effectiveness of FreeFish marketing and sales.